The Application of Government Accounting Standard towards Quality Village Government Financial Statement - Arnita, Vina; Zainal, Siti Rohaida Mohammed (Journal of Business and Economics Research (JBE), 2025)
This study aims to examine the application of Public Accounting Standards (PAS) towards the quality of local government financial statements, with a specific case study in Sidodadi Village. The research uses a quantitative approach, employing survey methods with questionnaires distributed to financial managers in local government institutions, particularly those involved in financial reporting within the village administration. The data were analyzed using simple linear regression analysis to test the relationship between PAS implementation and financial statement quality.The findings reveal that the effective application of PAS significantly improves the reliability, relevance, and comparability of local government financial reports. In the case of Sidodadi Village, the consistent use of PAS strengthens reporting practices, ensuring that financial statements accurately reflect village financial activities. Furthermore, compliance with PAS enhances transparency and accountability, thereby increasing stakeholder trust, particularly among community members and supervisory agencies.The originality of this research lies in its focus on the village-level government context, which has received relatively limited attention compared to studies on central government or private sector financial reporting. Additionally, it provides empirical evidence from developing country settings, contributing to the global understanding of public sector accounting practices. The practical implication is that policymakers and local government leaders, especially at the village level, should strengthen PAS implementation through training, monitoring, and evaluation to improve financial reporting quality. This will ultimately support better governance, resource allocation, and public service delivery in villages such as Sidodadi.